An impact of novel Terbium (Tb) doping on key opto-nonlinear optical characteristics of spray pyrolyzed NiO nanostructured films for opto-nonlinear applications. (February 2022) - Khan, Z.R.; Chandekar, Kamlesh V.; Khan, Aslam; Akhter, Naseem; Sayed, M.A.; Shkir, Mohd; Algarni, H.; AlFaify, S.
Abstract: This work reports an impact of novel Terbium (Tb) doping on physical characteristics of NiO nanostructured films. The doping concentrations of Tb varied from 0 to 5.0 wt% in NiO system and are characterized using various characterization techniques. Thin films show the cubic structure preferred orientation along (111). Sizes of crystallites of films increases with Tb doping contents and strain of the films decreases. Optical constants (such as energy gap, absorption and refractive indices) are examined as a function of Tb doping concentrations. Optical band gap showed a blue shift with Tb doping concentrations. In addition, 3rd order nonlinear susceptibility and refractive index have been noticed in range of 1.78 × 10 −14 -6.71 × 10 −11 esu and 7.62 × 10 −12 - 5.81 × 10 −10 esu; respectively. Room temperature photoluminescence spectra of films reveal band-to-band transitions in UV region. Above opto-nonlinear investigation of Tb:NiO nanostructured thin films reinforce the potential candidate for optoelectronics applications. Graphical abstract: Image 1